Tertiary care availability and adolescent pregnancy characteristics in Saudi Arabia - Al-Kadri HM; Madkhali A; Al-Kadi MT; Bakhsh H; Alruwaili NN; Tamim HM (Dove Medical Press, 2014)
Hanan M Al-Kadri,1 Azza Madkhali,1 Mohammed T Al-Kadi,2 Hanadi Bakhsh,1 Nourah N Alruwaili,2 Hani M Tamim21Department of Obstetrics and Gynecology, King Abdulaziz Medical City, King Saud Bin Abdulaziz University for Health Sciences, Riyadh, 2King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Kingdom of Saudi ArabiaBackground: In this study, we aimed to assess the rate of adolescent delivery in a Saudi tertiary health care center and to investigate the association between maternal age and fetal, neonatal, and maternal complications where a professional tertiary medical care service is provided.Methods: A cross-sectional study was performed between 2005 and 2010 at King Abdulaziz Medical City, Riyadh, Saudi Arabia. All primigravid Saudi women ≥24 weeks gestation, carrying a singleton pregnancy, aged <35 years, and with no chronic medical problems were eligible. Women were divided into three groups based on their age, ie, group 1 (G1) <16 years, group 2 (G2) ≥16 up to 19 years, and group 3 (G3) ≥19 up to 35 years. Data were collected from maternal and neonatal medical records. We calculated the association between the different age groups and maternal characteristics, as well as events and complications during the antenatal period, labor, and delivery.Results: The rates of adolescent delivery were 20.0 and 16.3 per 1,000 births in 2009 and 2010, respectively. Compared with G1 and G2 women, G3 women tended to have a higher body mass index, a longer first and second stage of labor, more blood loss at delivery, and a longer hospital stay. Compared with G1 and G2 women, respectively, G3 women had a 42% and a 67% increased risk of cesarean section, and had a 52% increased risk of instrumental delivery. G3 women were more likely to develop gestational diabetes or anemia, G2 women had a three-fold increased risk of premature delivery (odds ratio 2.81), and G3 neonates had a 50% increased overall risk of neonatal complications (odds ratio 0.51).Conclusion: The adolescent birth rate appears to be low in central Saudi Arabia compared with other parts of the world. Excluding preterm delivery, adolescent delivery cared for in a tertiary health care center is not associated with a significantly increased medical risk to the mother, fetus, or neonate. The psychosocial effect of adolescent pregnancy and delivery needs to be assessed.Keywords: adolescent pregnancy, maternal mortality, maternal morbidity, neonatal mortality, neonatal morbidity